* Pembaharuan Pemikiran Islam dan Relevansinya Bagi Pengembangan Pendidikan di Indonesia: Pembaharuan Pemikiran Islam - Abdul Hamid (STAI Tebing Tinggi Deli, 2019)
The issue of renewal will always be associated with the advancement of scienceand technology as well as the changing demands of the times. Modernization orrenewal can be an attempt to improve the situation both in terms of ways,concepts, and a set of methods commonly applied in order to deliver bettercircumstances. In the context of renewal education is the absolute thing to bedone because part of maintaining the existence of education itself. Islamiceducation is uniquely different from other types of educational theory andpractice largely because of the all-encompassing influence of the Qur’an. Therenewal of Islamic education is an attempt to actualize the great values ofreligion in the form of an empirical and historical life. Nurcholis Madjid andKuntowijoyo are two great Islamic thinkers of Indonesia who seek to actualizeIslamic values in everyday life. Although not specific in the world of education,but what is done in Islamic renewal can be used in renewal in education. Thevalues of religion that are still normative and subjective must be transformedinto theories that can be translated in the empirical world and becomeobjective. This paper aims to explore the thinking of Islamic renewal of thesetwo figures and find its relevance to the development of Islamic education